Penerapan Model Pembelajaran Take and Give Berbasis Media Video untuk Meningkatkan Motivasi Belajar Peserta Didik pada Muatan IPS Kelas V Sekolah Dasar - Nuraisah Jan Sabela; Muhammad Sofwan; Eka Sastrawati (Departement of Mathematics Education, 2024)
This study aims to describe the application of the video media-based Take and Give learning model to increase students' learning motivation in social studies content for class V Elementary School. This research was conducted at SDN 224/VII Mekarsari III, Pelawan District, Sarolangun Regency. The form of this research is classroom action research. The research data was obtained by means of observation, interviews and documentation. After that the data were analyzed qualitatively and quantitatively. This research was conducted in two cycles, with four stages namely planning, implementing, observing, and reflecting. Based on the results of research that applied the Take and Give learning model based on video media on social studies content, it was able to increase student learning motivation. This is because students experience an increase in motivation by paying attention to each indicator of motivation in their learning which can be seen in each meeting cycle. In cycle I it is known that the level of student motivation is only in the